The Effect of Murabahah, Ijarah and Qardh Receivables on Total Assets at Bank Syariah Mandiri Period 2011-2019 - Mutawali Mutawali (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The object of this research is PT. Bank Syariah Mandiri. This research was conducted because there were problems with Murabahah receivables that were too high, Ijarah that was too low, and fluctuating Qardh, which affected the fluctuating movement of total assets. This study aims to analyze the partial effect of Murabahah receivables on total assets, the partial effect of Ijarah receivables on total assets, the partial effect of Qardh receivables on total assets, and the simultaneous effect of Murabahah, Ijarah, and Qardh receivables on total assets in Bank Syariah Mandiri period. 2011-2019. This research uses descriptive quantitative research methods. The researchers used purposive sampling, namely the financial statements of the quarterly balance sheet of Bank Syariah Mandiri for the period 2011-2019. The data used is in the form of secondary data obtained from the financial statements of Bank Syariah Mandiri for the period 2011-2019, journals, and internet research. The analysis technique that the researcher uses multiple linear regression using SSS version 22 with the analysis stages of the classical assumption test, t statistical test, F statistical test, correlation coefficient test, and determination coefficient test. The results of the conclusion in this study are that there is a partial influence on Murabahah receivables on total assets, there is a partial effect of Ijarah's receivables on total assets, there is a partial effect on Qardh's receivables on total assets, and there is a simultaneous influence on Murabahah, Ijarah and Qardh receivables on total assets. assets at Bank Syariah Mandiri.